1993
DOI: 10.1002/1097-0142(19930601)71:11<3774::aid-cncr2820711147>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of taxol as a potential radiation sensitizer

Abstract: Background. The authors evaluated the effects of taxol, a microtubular inhibitor, as a possible radiation sensitizer on the human leukemic cell line (HL‐60). Taxol acts as a mitotic inhibitor, blocking cells in the G2M‐phase of the cell cycle. The differential radiation sensitivity of cells in various phases of the cell cycle has been well recognized. This study was focused on the possible interaction between radiation and a microtubular inhibitor, taxol, in regard to its ability to synchronize cells at the G2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(79 citation statements)
references
References 8 publications
0
78
1
Order By: Relevance
“…Paclitaxel is a microtubulestabilising agent that blocks the cell cycle in the G2 and M phase, the most radiosensitive phase. The radioenhancing effects of paclitaxel have been demonstrated in vitro in a human leukaemic cell line and in cell lines of squamous cell carcinoma and astrocytoma (Tishler et al, 1992;Choy et al, 1993;Leonard et al, 1996). Besides its radiosensitising effect, it also enhances the result of radiotherapy by increasing apoptosis and tumour reoxygenation.…”
mentioning
confidence: 99%
“…Paclitaxel is a microtubulestabilising agent that blocks the cell cycle in the G2 and M phase, the most radiosensitive phase. The radioenhancing effects of paclitaxel have been demonstrated in vitro in a human leukaemic cell line and in cell lines of squamous cell carcinoma and astrocytoma (Tishler et al, 1992;Choy et al, 1993;Leonard et al, 1996). Besides its radiosensitising effect, it also enhances the result of radiotherapy by increasing apoptosis and tumour reoxygenation.…”
mentioning
confidence: 99%
“…The results obtained with this combined treatment modality in vitro seem to be somewhat less than has been expected. Both supraadditive [3][4][5][6] and additive [7][8][9][10] results have been reported in a variety of malignant cell lines, but subadditive interaction has also been demonstrated in vitro. 11,12 Contradictory outcomes in cytotoxic studies on the mechanism of action of paclitaxel have thrown doubt on the accumulation in G 2 /M being the main reason for the antitumor activity of paclitaxel.…”
mentioning
confidence: 99%
“…Many reports have confirmed the radiosensitising effect of PTX in different cell lines (Tishler et al, 1992;Choy et al, 1993;Lokeshwar et al, 1995;Rodriguez et al, 1995), in vivo experiments (Milas et al, 1994Cividalli et al, 1998), and in several clinical trials of combined PTX with radiation therapy according to different schedules (Dillman et al, 1990;Arriagada et al, 1991;Morton et al, 1991;Furuse et al, 1999;Sause et al, 2000;Chen et al, 2003). Chen et al (2003) examined the optimal timing of PTX treatment and irradiation in relation to the cell cycle, and recommended that radiation be given at least 5 h after PTX administration, because G2/M arrest of a lung cancer cell line was shown to start at 4 h after PTX treatment and to last for 44 h.…”
Section: Discussionmentioning
confidence: 90%
“…Besides its antitumour activity, its ability to induce radiosensitisation has been reported both in vitro (Tishler et al, 1992;Choy et al, 1993;Lokeshwar et al, 1995;Rodriguez et al, 1995) and in vivo (Milas et al, 1994Cividalli et al, 1998) this effect has been attributed to its effect of stabilising microtubules and inducing cell cycle arrest at the G2/M phase, the most radiosensitive phase of the cell cycle (Terasima and Tolmach, 1963;Sinclair and Morton, 1966). As several clinical studies have demonstrated the efficacy of PTX-based chemotherapy combined with radiotherapy, the combined modality is considered to be a potentially important treatment option for lung and breast cancer (Choy et al, 1998a(Choy et al, , b, 2000Dowell et al, 1999;Formenti et al, 2003;Kao et al, 2005).…”
mentioning
confidence: 99%